An Anatomical Substrate for the Spatiotemporal Transformation - Moschovakis, A. K. (J Neurosci, 1998)
The purpose of the present experiments was to test the hypothesis that the metrics of saccades caused by the activation of distinct collicular sites depend on the strength of their projections onto the burst generators. This study of morphofunctional correlations was limited to the horizontal components of saccades. We evoked saccades by stimulation of the deeper layers of the superior colliculus (SC) in alert, head-fixed cats. We used standard stimulus trains of 350 msec duration, 200 Hz pulse rate, and intensity set at two times saccade threshold in all experiments. Evoked saccades were analyzed quantitatively to determine the amplitude of the horizontal component of their “characteristic vectors”. This parameter is independent of eye position and was used as the physiological, saccade-related metric of the stimulation sites. Anatomical connections arising from these sites were visualized after anterograde transport of biocytin injected through a micropipette adjoining the stimulation electrode. The stimulation and injection sites were, therefore, practically identical. We counted boutons deployed in regions of the paramedian pontine reticular formation reported to contain long-lead and medium-lead burst neurons of the horizontal burst generator. Regression analysis of the normalized bouton counts revealed a significant positive correlation with the size of the horizontal component of the characteristic vectors. This data supports a frequent modelling assumption that the spatiotemporal transformation in the saccadic system relies on the graded strength of anatomical projections of distinct SC sites onto the burst generators.